2006
DOI: 10.1002/adfm.200500891
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Design of Catalysts for the Heterolytic Splitting of H2

Abstract: Here, we briefly review recent advances in H2 storage technologies relying on mixed proton–hydride and destabilized hydride materials. We establish a general relationship across different materials: the higher the effective H content, the higher the temperatures needed to completely desorb H2. Nevertheless, several systems show promising thermodynamics for H2 desorption; however, the desorption kinetics still needs to be improved by the use of appropriate catalysts. Prompted by the importance of heterolyticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…So far we have discussed compounds of Xe and Kr in their positive oxidation states, predominantly those of divalent Ng The calculated structures of: (A) Xe VI F 5 Cl in C 4v symmetry; (B) Xe IV F 3 Cl in C 2v symmetry; (C) Xe IV F 3 (C 2 F) in C 2v symmetry; (D) FXe II SiF 3 in C 3v symmetry; (E) HXe II OOXe II H in C 2 symmetry; (F) FXe II OOXe II F in C 2 symmetry; note, the O-O bond is shorter than for HXe II OOXe II H; (G) FXe II (NF)Xe II F in C s symmetry; (H) ClXe II FXe II Cl + in D 'h symmetry. 146 Most of these compounds (A-G) are predicted to be unstable thermodynamically with respect to the substrates (eqn (12)- (17), but they are genuine minima on the PES's. Calculated bond lengths are given in Å .…”
Section: A Xe Atom Is Just a Lewis Basementioning
confidence: 99%
“…So far we have discussed compounds of Xe and Kr in their positive oxidation states, predominantly those of divalent Ng The calculated structures of: (A) Xe VI F 5 Cl in C 4v symmetry; (B) Xe IV F 3 Cl in C 2v symmetry; (C) Xe IV F 3 (C 2 F) in C 2v symmetry; (D) FXe II SiF 3 in C 3v symmetry; (E) HXe II OOXe II H in C 2 symmetry; (F) FXe II OOXe II F in C 2 symmetry; note, the O-O bond is shorter than for HXe II OOXe II H; (G) FXe II (NF)Xe II F in C s symmetry; (H) ClXe II FXe II Cl + in D 'h symmetry. 146 Most of these compounds (A-G) are predicted to be unstable thermodynamically with respect to the substrates (eqn (12)- (17), but they are genuine minima on the PES's. Calculated bond lengths are given in Å .…”
Section: A Xe Atom Is Just a Lewis Basementioning
confidence: 99%
“…Another broadly explored attempt to facilitate hydrogen release is the formation of protonic-hydridic compounds [291] via a combination of the moieties containing partially negatively charged H atoms bound to boron with those attached to nitrogen, which are partially positive. Such approach often increases the theoretical gravimetric content of hydrogen and lowers the temperature of decomposition, as compared with similar borohydrides lacking nitrogen [292].…”
Section: Properties and Prospective Applicabilitymentioning
confidence: 99%
“…This feature only in part reflects the obstacles that arise from thermodynamics; some of the mixed H + /H À (and 'destabilized') materials for hydrogen storage could, in principle, exhibit much lower values of the thermal decomposition temperature, if proper catalysts are used. 5 Previously, we have reported that the hypothetical Ti 4 C 4 H 6 molecule is capable of low-barrier (B0.3 eV) heterolytic splitting and attachment of H 2 . 6 Unfortunately, H 2 binds too strongly to Ti 4 C 4 H 6 (by B1.0 eV) to be detached at modest temperatures.…”
Section: Introductionmentioning
confidence: 97%
“…This finding has triggered a set of systematic investigations of the related M 4 Nm 4 H 6 molecules (M = Ti, Zr, Hf, V, Nm = C, Si, B, N). 5 We have found that the molecular species containing the coordinatively unsaturated 4TiQSio or 4ZrQSio units, such as the M 4 Si 4 H 6 molecules (M = Ti, Zr), exhibit favourable thermodynamics and extremely small barriers for the attachment of H 2 . At that time we considered exclusively isomers, which are denoted here as I, II and III (see Section 2 of the present work).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation